Tension Hemopneumothorax in the Setting of Mechanical CPR during Prehospital Cardiac Arrest. (23rd February 2021) - Rowland, Dustin; Vryhof, Nicholas; Overton, David; Mastenbrook, Joshua
Abstract: Introduction: There are several complications associated with automated mechanical CPR (AM-CPR), including tension pneumothoraces. The incidence of these complications and the risk factors for their development remain poorly characterized. Tension hemopneumothorax is a previously unreported complication of AM-CPR. The authors present a case of a suspected tension hemopneumothorax that developed during the use of an automated mechanical CPR device. Case Description: A 67 year-old woman with a history of COPD and CABG was observed by an off-duty firefighter to be slumped behind the wheel of an ice cream truck that drifted off the road at a low rate of speed and was stopped by a wooden fence, resulting in only minor paint scratches. The patient was found to be in cardiac arrest with a shockable rhythm. No signs of trauma were noted, and equal bilateral breath sounds were present with BVM ventilation. After 13 minutes of manual CPR, fire department personnel applied their Defibtech LifeLine ARM mechanical CPR device to the patient. During resuscitation, the device had to be repositioned twice due to rightward piston migration off of the sternum. Seven minutes after AM-CPR application, the patient had absent right-sided breath sounds and ventilations were more difficult. Needle decompression was performed with an audible release of air. A chest tube was placed by an EMS physician and roughly 400 mL of blood were immediately returned. At the next 2-minute pulse check, ROSC was noted, and the patient was transported to the hospital. She had an ischemic EKG and elevated troponin. Chest CT showed emphysematous lungs, bilateral rib fractures, and a small right-sided pneumothorax. Despite aggressive measures, the patient's condition gradually worsened, and she died 48 hours after presentation. Discussion/Conclusion: Migration of AM-CPR device pistons may contribute to the development of iatrogenic injuries such as hemopneumothoraces. Patients with underlying lung disease may be at a higher risk of developing pneumothoraces or hemopneumothoraces during the course of AM-CPR. Awareness of these potential complications may aid first responders by improving vigilance of piston location and by providing quicker recognition of iatrogenic injuries that need immediate attention to improve the opportunity for ROSC.